Seismic evidence for a mantle suture and implications for the origin of the Canadian Cordillera - Chen, Yunfeng; Gu, Yu Jeffrey; Currie, Claire A.; Johnston, Stephen T.; Hung, Shu-Huei; Schaeffer, Andrew J.; Audet, Pascal (Nature communications, 2019)
The origin of the North American Cordillera and its affinity with the bounding craton are subjects of contentious debate. The mechanisms of orogenesis are rooted in two competing hypotheses known as the accretionary and collisional models. The former model attributes the Cordillera to an archetypal accretionary orogen comprising a collage of exotic terranes. The latter, less popular view argues that the Cordillera is a collisional product between an allochthonous ribbon microcontinent and cratonic North America. Here we present new seismic evidence of a sharp and structurally complex Cordillera–craton boundary in the uppermost mantle beneath the southern Canadian Cordillera, which can be interpreted as either a reshaped craton margin or a Late Cretaceous collisional boundary based on the respective hypotheses. This boundary dips steeply westward underneath a proposed (cryptic) suture in the foreland, consisent with the predicted location and geometry of the mantle suture, thus favoring a collisional origin. Two challenging theories, accretion versus collision, approach the orogenesis of the North American Cordillera. Here, the authors present new, high-resolution geophysical datasets consistent with a model of collision in response to westward subduction of the North American craton.